Colorectal Carcinoma in the Background of Pelvic Inflammatory Disease - M Ammar Kalas MD; Sara Alhariri MD; Andrew Jonathen Ortega DO; Gian Marco Galura MD; Ihsan Al Bayati MD; Sarah Al Obaidi MD (SAGE Publishing, 2022)
Colorectal carcinoma (CRC) is a common malignancy with steadily declining incidence rates and mortality, secondary to improved screening and lifestyle changes (eg, decreased smoking rates). The association between pelvic inflammatory disease (PID) and CRC has been unclear in the past. However, multiple studies showed a positive association between PID and underlying malignancy (gynecologic and pelvic primarily). Several studies evaluated the relation between PID and CRC, but the results were conflicting. We describe a case of a 33-year-old female patient, with a history of PID and recurrent pelvic abscesses, who was found to have CRC. Of note, the patient's diagnosis was based on abnormal computed tomography findings, which were further investigated (by colonoscopy and biopsy), rather than on symptoms suggestive of CRC, such as rectal bleeding, constipation, symptomatic anemia, or abdominal pain.